1.15 Å resolution structure of the proteasome-assembly chaperone Nas2 PDZ domain - Singh, Chingakham R.; Lovell, Scott; Mehzabeen, Nurjahan; Chowdhury, Wasimul Q.; Geanes, Eric S.; Battaile, Kevin P.; Roelofs, Jeroen (My University, 2014)
The 26S proteasome is a 2.5 MDa protease dedicated to the degradation of ubiquitinated proteins in eukaryotes. The assembly of this complex containing 66 polypeptides is assisted by at least nine proteasome-specific chaperones. One of these, Nas2, binds to the proteasomal AAA-ATPase subunit Rpt5. The PDZ domain of Nas2 binds to the C-terminal tail of Rpt5; however, it does not require the C-terminus of Rpt5 for binding. Here, the 1.15 Å resolution structure of the PDZ domain of Nas2 is reported. This structure will provide a basis for further insights regarding the structure and function of Nas2 in proteasome assembly.
Keywords: 26S proteasome; Proteasome-assembly; Nas2 PDZ domain